Differential cognitive functioning in the digital clock drawing test in AD-MCI and PD-MCI populations - Wang, Chen; Li, Kai; Huang, Shouqiang; Liu, Jiakang; Li, Shuwu; Tu, Yuting; Wang, Bo; Zhang, Pengpeng; Luo, Yuntian; Chen, Tong (Frontiers in Neuroscience, 2025)
BackgroundMild cognitive impairment (MCI) is common in Alzheimer’s disease (AD) and Parkinson’s disease (PD), but there are differences in pathogenesis and cognitive performance between Mild cognitive impairment due to Alzheimer’s disease (AD-MCI) and Parkinson’s disease with Mild cognitive impairment (PD-MCI) populations. Studies have shown that assessments based on the digital clock drawing test (dCDT) can effectively reflect cognitive deficits. Based on this, we proposed the following research hypothesis: there is a difference in cognitive functioning between AD-MCI and PD-MCI populations in the CDT, and the two populations can be effectively distinguished based on this feature.MethodsTo test this hypothesis, we designed the dCDT to extract digital biomarkers that can characterize and quantify cognitive function differences between AD-MCI and PD-MCI populations. We enrolled a total of 40 AD-MCI patients, 40 PD-MCI patients, 41 PD with normal cognition (PD-NC) patients and 40 normal cognition (NC) controls.ResultsThrough a cross-sectional study, we revealed a difference in cognitive function between AD-MCI and PD-MCI populations in the dCDT, which distinguished AD-MCI from PD-MCI patients, the area under the roc curve (AUC) = 0.923, 95% confidence interval (CI) = 0.866–0.983. The AUC for effective differentiation between AD-MCI and PD-MCI patients with high education (≥12 years of education) was 0.968, CI = 0.927–1.000. By correlation analysis, we found that the overall plotting of task performance score (VFDB1) correlated with the [visuospatial/executive] subtest score on the Montreal Cognitive Assessment (MoCA) scale (Spearman rank correlation coefficient [R] = 0.472, p < 0.001).ConclusionThe dCDT is a tool that can rapidly and accurately characterize and quantify differences in cognitive functioning in AD-MCI and PD-MCI populations.